2012
DOI: 10.1111/j.1365-3083.2011.02637.x
|View full text |Cite
|
Sign up to set email alerts
|

Healthy First‐Degree Relatives of Patients with Type 1 Diabetes Exhibit Significant Differences in Basal Gene Expression Pattern of Immunocompetent Cells Compared to Controls: Expression Pattern as Predeterminant of Autoimmune Diabetes

Abstract: Expression features of genetic landscape which predispose an individual to the type 1 diabetes are poorly understood. We addressed this question by comparing gene expression profile of freshly isolated peripheral blood mononuclear cells isolated from either patients with type 1 diabetes (T1D), or their first‐degree relatives or healthy controls. Our aim was to establish whether a distinct type of ‘prodiabetogenic’ gene expression pattern in the group of relatives of patients with T1D could be identified. Whole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
24
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 45 publications
(55 reference statements)
4
24
0
Order By: Relevance
“…First-degree relatives of T1D patients, independently by the presence or not of autoantibodies, showed up-regulation of TLR2, TLR6 and TIRAP in respect with healthy controls. This observation supports the idea that autoantibody-negative healthy relatives showed however a different regulation of several immune-related signaling pathways [62], accordingly with the presence of proinflammatory islet-selective T cell responses observed in these subjects by the group of de Marquesini [102].…”
Section: Accepted Manuscriptsupporting
confidence: 66%
See 2 more Smart Citations
“…First-degree relatives of T1D patients, independently by the presence or not of autoantibodies, showed up-regulation of TLR2, TLR6 and TIRAP in respect with healthy controls. This observation supports the idea that autoantibody-negative healthy relatives showed however a different regulation of several immune-related signaling pathways [62], accordingly with the presence of proinflammatory islet-selective T cell responses observed in these subjects by the group of de Marquesini [102].…”
Section: Accepted Manuscriptsupporting
confidence: 66%
“…These cells begin the infiltration of the pancreas and, through the release of cytokines, support cytotoxic T lymphocytes (Tc) which are responsible for the progressive destruction of  cells [62]. Although the etiology must be yet elucidated, a combination of environmental, genetic and stochastic factors contributes to its pathogenesis [87,88,90].…”
Section: Accepted Manuscriptmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, although a pre-diabetic stage of the quadruplet C correlates with a more recent occurrence of enteroviral infection, its positivity for anti-islet autoantibodies GAD65 and IA-2A indicates that this infection might not be a primary cause of the antiislet autoimmunity, which rather results from a genetic predisposition of quadruplets to diabetes. 44 This line of arguments is further supported by a recent study suggesting that the progression from islet autoimmunity to fully blown T1D may increase after an enterovirus infection. 15 In this respect, the timing of infection and its periodic recurrence as well as a dose of the virus are certainly important parameters when considering the effect of viral infection on the same diabetes-susceptible genetic background.…”
Section: Discussionmentioning
confidence: 65%
“…Moreover, the highest number of differentially activated cell signalling processes (99 pathways) was reported in the comparison between the relatives, regardless of autoantibody status, and the control group. Interestingly, DNA damage and oxidative stress were among those pathways (Stechova et al 2011). Thus, these findings showed that non-diabetic relatives of T1DM patients also present alterations in the expression of genes.…”
Section: Transcriptional Expression Of Protein-coding Genes and Micromentioning
confidence: 63%